Calcium Regulation of Myogenesis by Differential Calmodulin Inhibition of Basic Helix-Loop-Helix Transcription Factors - Hauser, Jannek (The American Society for Cell Biology, 2008)
The members of the MyoD family of basic helix-loop-helix (bHLH) transcription factors are critical regulators of skeletal muscle differentiation that function as heterodimers with ubiquitously expressed E-protein bHLH transcription factors. These heterodimers must compete successfully with homodimers of E12 and other E-proteins to enable myogenesis. Here, we show that E12 mutants resistant to Ca(2+)-loaded calmodulin (CaM) inhibit MyoD-initiated myogenic conversion of transfected fibroblasts. Ca(2+) channel blockers reduce, and Ca(2+) stimulation increases, transcription by coexpressed MyoD and wild-type E12 but not CaM-resistant mutant E12. Furthermore, CaM-resistant E12 gives lower MyoD binding and higher E12 binding to a MyoD-responsive promoter in vivo and cannot rescue myogenic differentiation that has been inhibited by siRNA against E12 and E47. Our data support the concept that Ca(2+)-loaded CaM enables myogenesis by inhibiting DNA binding of E-protein homodimers, thereby promoting occupancy of myogenic bHLH protein/E-protein heterodimers on promoters of myogenic target genes.